The dark side of herbal medicine - risks of Ashwagandha (Withania Somnifera) consumption - Burda, Katarzyna; Czarnecka, Karolina; Łopacińska, Olga; Stańczyk, Katarzyna; Korn, Aleksandra; Wójcik, Emilia; Korczak, Anna; Jędrzejczyk, Justyna; Szewczyk, Oliwia; Olek, Ewa (Journal of Education, Health and Sport, 2024)
Introduction: Herbal medicine has been growing in popularity over the last few years. One of the most often used herbal remedy is Withania somnifera, more widely known as Ashwagandha Now known for its anti-stress, anti-inflammatory, antioxidant, anti-cancer, anti-anxiety properties it ranks as a cure-all. However, there is a rising amount of alarming reports regarding its safety. It has been observed that its effects are not always beneficial, and for some patients the risks of taking it may be greater than the promoted benefits. Aim of study: The aim of this paper is to evaluate possible risks connected to Withania Somnifera consumption based on available research articles and case reports. Materials and methods: This article is based on the literature found in the PubMed Database from the period of 2004-2024 with the use of keywords such as “Ashwagandha”; “Withania Somnifera”, “herbal medicine”;”complementary medicine”;“liver injury”; “thyrotoxicosis”; “adrenal insufficiency”;”autoimmune diseases”. Results: The outcomes of all the reviewed studies in this paper indicate that Withania Somnifera might cause a wide range of side effects. They include herb induced liver injury, endocrine complications such as thyrotoxicosis and adrenal insufficiency, acute graft rejection in a kidney transplant recipient and possible contribution to the onset of new autoimmune disease in patient with the history of autoimmune disorders. Conclusion: Further long-term research is needed on the Ashwaghanda’s benefits but particularly on its safety and potential side effects. The common education on the risks of taking herbal supplements should be carried out among health professionals and the rest of the society. Ashwagandha should not be used by patients with liver, endocrine and autoimmune disorders as well as transplant recipients.